Applying a quantitative fire risk assessment method in hospital settings: Case study - Marzieh Beljikangarlou; Ali Ghazvinloo; Alireza Dehdashti; Mohammad Reza MirLavasani (PLoS ONE, 2025)
Understanding and mitigating fire risks in healthcare settings are crucial for ensuring the safety of individuals, especially during the current pandemic, which has increased the use of oxygen-supply equipment and potentially raised fire hazards. This case study, conducted in two university hospitals in Semnan, Iran, examined fire risk factors in healthcare facilities using a developed fire risk assessment method. A total of 28 wards and 74 compartments were assessed. Data collection included topographical structure analysis, building usage evaluation, and process documentation review. The FRAME method, validated in previous studies, was used to calculate fire risk levels for buildings, contents, occupants, and activities. The fire risk assessment revealed varying risk levels across different wards and compartments in the two hospitals. Hospital A exhibited higher fire risk levels compared to Hospital B, with several wards in Hospital A classified as "High" or "Very High" risk. Factors contributing to higher risk levels included building design, occupancy density, and the presence of flammable materials. Occupants in certain wards, particularly those with high occupancy rates and limited evacuation routes, were identified as being at increased risk. Activities such as the storage and handling of flammable materials were also found to contribute to elevated risk levels in specific areas. The study emphasizes the importance of implementing targeted fire safety measures, especially regarding oxygen-supplying equipment, high-density ventilators, and limited escape routes, to mitigate risks effectively in healthcare settings. This comprehensive assessment can guide best practices in fire safety management in hospitals.